2020
DOI: 10.3390/antiox9090837
|View full text |Cite
|
Sign up to set email alerts
|

Different Nitro-Oxidative Response of Odontarrhena lesbiaca Plants from Geographically Separated Habitats to Excess Nickel

Abstract: Odontarrhena lesbiaca is an endemic species to the serpentine soils of Lesbos Island (Greece). As a nickel (Ni) hyperaccumulator, it possesses an exceptional Ni tolerance; and it can accumulate up to 0.2–2.4% Ni of its leaves’ dry weight. In our study, O. lesbiaca seeds from two geographically separated study sites (Ampeliko and Loutra) were germinated and grown on control and Ni-containing (3000 mg/kg) soil in a rhizotron system. Ni excess induced significant Ni uptake and translocation in both O. lesbiaca ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…O. lesbiaca is the only hyperaccumulator species in our communities, with differences in Ni hyperaccumulation among its populations being consistent with nickel availability in the soil (Kazakou et al 2010; Adamidis et al 2014c). In a rhizotron experiment, individuals of O. lesbiaca from Ni rich soils (Ampeliko) proved to be more tolerant in terms of root growth relative to those from sites with lower nickel content (Loutra), as Ni-induced nitric oxide accumulation was observed in their root tips along with a decrease in the degree of protein tyrosine nitration (Feigl et al 2020). The difference in traits of the O. lesbiaca could also be linked to high resistance to low nutrient and water availability (Kazakou et al 2008; Harrison et al 2017), as species strictly restricted to serpentine habitats are found to have higher drought tolerance than more generalist Mediterranean species (Hidalgo-Triana et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…O. lesbiaca is the only hyperaccumulator species in our communities, with differences in Ni hyperaccumulation among its populations being consistent with nickel availability in the soil (Kazakou et al 2010; Adamidis et al 2014c). In a rhizotron experiment, individuals of O. lesbiaca from Ni rich soils (Ampeliko) proved to be more tolerant in terms of root growth relative to those from sites with lower nickel content (Loutra), as Ni-induced nitric oxide accumulation was observed in their root tips along with a decrease in the degree of protein tyrosine nitration (Feigl et al 2020). The difference in traits of the O. lesbiaca could also be linked to high resistance to low nutrient and water availability (Kazakou et al 2008; Harrison et al 2017), as species strictly restricted to serpentine habitats are found to have higher drought tolerance than more generalist Mediterranean species (Hidalgo-Triana et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Transfer and accumulation of metals from soil to plants is complex and often site-specific. Factors influencing this include: the chemical forms of the heavy metal; the pH of the soil; the soil organic matter content; soil nutrient contents; root exudation of organic acids and flavonoids; soil texture (particularly clay content); mycorrhizal symbiosis, microbial activity and abundance; the plant species; the plants stage of growth; climatic conditions and irrigation with polluted waters (Aladesanmi et al, 2019;Claveria et al, 2019b;Dahilan and Dalagan, 2017;de la Torre et al, 2016;De Oliveira et al, 2020;Domingo and David, 2014;Feigl et al, 2020;Mahajan et al, 2016;Navarrete et al, 2017;Sanqui et al, 2020;Susaya et al, 2010;Tibbett et al, 2021;Yashim et al, 2014).…”
Section: Metal Partitioning and Phytoextraction/phytomining Potentialmentioning
confidence: 99%
“…The use of soil-filled rhizotrons can be a good compromise between in vitro systems and field studies, allowing real-time, non-invasive studies of root system development [48]. Root responses of agricultural crops to different stressors have been investigated in such systems in several cases, e.g., treated with zinc [49] or nickel [50], combined heavy metal treatment modeling wastewater [51], polypropylene surgical mask fragments [52], or raw and nutrient-enriched pomegranate peel powder [53].…”
Section: Introductionmentioning
confidence: 99%